Penerapan Metode K-Means Clustering pada Hasil Produksi Beras di Wilayah Sumatera Utara - Rizki Risdah Sitorus; Rafiqi Aidil Fitra (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aims to apply the method K-Means Clustering on rice production results in the region North Sumatra. K-Means Clustering is a data analysis technique that is useful for grouping data into several groups based on similar characteristics. This research uses rice production data from several districts/cities in North Sumatra as samples. The K Means method is used to group these regions into several clusters based on rice production they. The research results show that the K Means Clustering method can be used for identification rice production patterns in the North Sumatra region. The hope is, research results can be a valuable contribution, provide recommendations, and support initiatives for the North Sumatra provincial government in improving rice production throughout the region, with the aim of ensuring a more stable food supply for the community.